Cyclamin, a Natural 13,28-Epoxy Triterpenoid Saponin, Synergistically Enhances the Cytotoxicity of Chemotherapeutic Drugs in Human Liver Cancer Cells but Not Non-Neoplastic Liver Cells - Li, Qin; Deng, Lin; Li, Wei; Koike, Kazuo (Planta Medica, 2014)
In this study, a diverse set of triterpenoid saponins was evaluated to assess their chemosensitizing activity in two human liver cancer cells (Bel-7402 and HepG2) and non-neoplastic HL-7702 liver cells. Cyclamin, a 13,28-epoxy oleanane-type triterpenoid saponin from Ardisia japonica, was identified as a potent chemosensitizer. A low cytotoxic level of cyclamin synergistically enhances the growth inhibitory effect of 5-fluorouracil (from 41.3 ± 1.1 % to 64.5 ± 2.3 %), cisplatin (from 57.1 ± 1.5 % to 79.6 ± 2.7 %), and epirubicin (from 62.6 ± 1.2 % to 74.9 ± 1.8 %) on Bel-7402 cells, but not HL-7702 cells. Flow cytometric analysis shows that cyclamin synergistically enhances the apoptosis and cell cycle arrest induction effects of 5-fluorouracil by 69.4 % and 22.2 %, respectively. The mechanism of action could be through the activation of caspase-3, -8, and -9, the upregulation of cyclin-dependent kinase 2, the cell division cycle 25 homolog A expression level, or the Bax/B-cell lymphoma 2 ratio. Furthermore, a lactate dehydrogenase release assay demonstrated that cyclamin markedly increases the membrane permeability of Bel-7402 cells, which may also contribute to the mechanism of the chemosensitizing activity of cyclamin. These findings indicate the potential usefulness of cyclamin for the chemoprevention and treatment of liver cancer.
Keywords: Ardisia japonica; Myrsinaceae; cyclamin; chemosensitizer; liver cancer; permeability; cytotoxicity